Math, asked by kumar789456321, 11 months ago

find the value of K
( \frac{ - 5}{11} ) {}^{k + 2}  \div ( \frac{ - 5}{11}  )  {}^{ - 4k + 5}  = (  \frac{ - 5}{11}  {}^{2k}

Answers

Answered by spacelover123
1

Since the base numbers are the same, we will apply the exponent power law which is ⇒ \frac{a^{m}}{a^{n}} =a^{m}\div a^{n} = a^{m-n}

So here the equation would be ⇒

(k+2)-(-4k+5)=2k

Step 1: Simplify both sides of the equation.

k+2-(-4k+5)=2k

(Distribute the Negative Sign)

k+2+-1(-4k+5)=2k

k+2+-1(-4k)+(-1)(5)=2k

k+2+4k+-5=2k

(Combine Like Terms)

(k+4k)+(2+-5)=2k

5k+-3=2k

5k-3=2k

Step 2: Subtract 2k from both sides.

5k-3-2k=2k-2k

3k-3=0

Step 3: Add 3 to both sides.

3k-3+3=0+3

3k=3

Step 4: Divide both sides by 3.

\frac{3k}{3}=\frac{3}{3}

k=1

Verification if k=1

(1+2)-((-4\times 1)+5)

3-(-4+5)

3-1

2

2\times 1 = 2

k=1 in the equation (\frac{-5}{11})^{k+2}\div(\frac{-5}{11})^{-4k+5}=(\frac{-5}{11})  ^{2k}

Additional Information ❤

What is an equation?

A statement that shows the equality of two expressions is known as an equation.

What are the types of equation?

There are five types of equations. They are as follows.

  • Polynomial Equation
  • Quadratic Equation
  • Rational Polynomial Equation
  • Trigonometric Equation
  • Cubic Equation
Answered by utsav96
1
Pls mark as brainliest answer
Attachments:
Similar questions